SOSIALISASI DAN EDUKASI PENCEGAHAN COVID-19 BAGI MASYARAKAT DI KELURAHAN SUKAJAYA KOTA PALEMBANG - Pusnita, Indah; Dewi, Inne Miftah; Junita, Den Eci; Juanda, Eri (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2020)
The COVID-19 pandemic has had a significant impact on various aspects of life, particularly in health, social, and economic sectors. Government prevention efforts, such as implementing health protocols, vaccination programs, and social restrictions, require active public participation to be effective. However, public awareness and compliance with health protocols remain challenges in controlling the pandemic. This study aims to evaluate the effectiveness of socialization and education activities on COVID-19 prevention conducted in RT 68 RW 10, Sukajaya Subdistrict, Sukarami District, Palembang City. The methods used include initial observations, educational material presentations, interactive discussions, demonstrations of health protocols, and the distribution of educational media. The results show an increase in public understanding of COVID-19 and the importance of implementing health protocols. However, challenges remain in ensuring consistent public adherence to these protocols. Therefore, a more sustainable educational strategy is needed, involving community leaders and utilizing digital media to raise awareness and reduce misinformation. With synergy between the government, academics, and the community, COVID-19 prevention efforts can be more optimal and contribute to long-term behavioral changes.